Prospective evaluation of the impact of repeated whole prison testing for hepatitis C - Stuart McPherson; Naw April Phaw; Manoj Valappil; Carolyn Miller; Craig Thompson; Francesca McCullough; Caroline Allsop; Kate McQue; Ryan Jelley; Jenna Kerry; Jodi Aldridge; Tony Jefferson; et al. (BMJ Open Gastroenterology)
Introduction Chronic hepatitis C virus (HCV) infection is prevalent in prisons. Universal reception HCV testing is recommended, but acceptance can be suboptimal. To detect and treat missed HCV infections, a high-intensity test and treat (HITT) programme was introduced to rapidly test entire prisons. It remains unknown whether regular HITTs will be required to maintain prison microelimination. We aimed to assess the outcomes of HITTs conducted in a prison 4 years apart with ongoing reception testing.Methods A prospective observational evaluation of the impact of HITTs was conducted in January 2020 and February 2024 at Low Newton, a female prison. The outcomes of the reception testing were reviewed in the intervening period to determine the number of newly identified HCV infections.Results HITTs were successful in testing almost all residents (305/307) in 2020 and (296/296) in 2024. The number of newly diagnosed HCV individuals fell from 6.6% in 2020 to 0.3% in 2024. One new HCV case was identified in the second HITT. In between the HITTs, 89% of receptions had HCV testing, increasing from 83% in 2020 to 95% in 2023. Overall, 81% (144/178) of active HCV infections received antiviral treatment, and 89% achieved sustained virological response. The proportion of active HCV infections between the HITTs was 7.2% through reception testing.Conclusion A follow-up HITT after 4 years yielded only 0.3% active HCV infection in a high HCV prevalence prison and a reasonably good reception testing and treatment programme. Therefore, resources should be focused on optimising reception testing rather than undertaking repeated HITTs.